The Implementation of Fuzzy Inference System for Predicting the Price of Oil Palm Fruit at PT. Tri Bahtera Srikandi - Ayu Hantira; Nuraisana (CV. ADMITECH SOLUTIONS, 2024)
Technology is widely implemented in various fields, especially in the field of oil palm fruit plantations. Oil palm plantations are one of the industrial sectors that directly benefit from the development of digital technology. Currently, many new innovations and technologies are emerging that can increase the productivity and welfare of oil palm farmers while maintaining the quality of the plants from time to time to maintain the price of oil palm fruit. PT. Tri Bahtera Srikandi is a palm oil mill that produces palm fruit into oil or CPO (Crude Palm Oil). Determining the price of oil palm fruit aims to provide fair prices to plantations and companies so that there are no losses from any party. However, the problem that arises is that when the price of palm oil fruit falls or increases periodically, the company will experience the risk of loss and uncertainty caused by fluctuations in the price of palm oil fruit. It is impossible for a company to be able to accommodate too much oil palm fruit for a long time so that if palm fruit is piled up, rot will occur in the palm oil fruit and this can affect production results and the amount of available oil or CPO (Crude Palm Oil). Therefore, it is important to predict the price of oil palm fruit in the future. Application of using the Tsukamoto fuzzy logic method in predicting the price of oil palm fruit at PT. Tri Bahtra Srikandi. It can be implemented in predicting the price of oil palm fruit accurately.